Engineering enzyme-cleavable oligonucleotides by automated solid-phase incorporation of cathepsin B sensitive dipeptide linkers - Jin, C; Sagheer, AHE; Li, S; Vallis, KA; Tan, W; Brown, T (Wiley, 2022)
Oligonucleotides containing cleavable linkers have emerged as versatile tools to achieve stimulus-responsive and site-specific cleavage of DNA. However, the limitations of previously reported cleavable linkers including photolabile and disulfide linkers have restricted their applications in vivo . Inspired by the cathepsin B-sensitive dipeptide linkers in antibody-drug conjugates (ADCs) such as Adcetris, we have developed Val-Ala-02 and Val-Ala-Chalcone phosphoramidites for the automated synthesis of enzyme-cleavable oligonucleotides. Cathepsin B digests Val-Ala-02 and Val-Ala-Chalcone linkers efficiently, enabling cleavage of oligonucleotides into two components or release of small-molecule payloads. Based on the prior success of dipeptide linkers in ADCs, we believe that these dipeptide linker phosphoramidites will promote new clinical applications of therapeutic oligonucleotides.